TEKNOLOGI ARTIFICIAL INTELLIGENCE DAN POTENSI PEMANFAATNYA DALAM KONSELING ONLINE DI MASA DEPAN - Haryadi, Rudi; Matarif, Jamaluddin; Budiono, Kabul (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2019)
Counseling activities that we usually carry out are usually face-to-face processes, as the times develop, counseling activities turn into online counseling where counseling uses technology intermediaries including chat, email, video conferencing, audio, and so on. But in the future with highly developed technology that is rapidly advancing online counseling based on Artificial Intelligence (AI) will be born with a new breakthrough that is more effective and efficient in future online counseling services, for that in this article the author will discuss online counseling, Artificial Intelligence (AI), the potential use of Artificial Intelligence (AI) in online counseling in the future, and differences in artificial intelligence and natural intelligence.